Transcatheter Tricuspid Valve Therapy: From Anatomy to Intervention - Cammalleri, Valeria; Carpenito, Myriam; Bono, Maria Caterina; Mega, Simona; Ussia, Gian Paolo; Grigioni, Francesco (Frontiers in Cardiovascular Medicine, 2021)
Nowadays, severe symptomatic tricuspid regurgitation (TR) affects millions of persons worldwide. However, the benefit of surgical correction of isolated secondary TR remains controversial because of the increased risk of periprocedural mortality and morbidity. In recent years, novel transcatheter tricuspid valve interventions (TTVI) were developed to treat TR, so that TTVI is currently considered in symptomatic, inoperable, anatomically eligible patients. TTVI can be divided into these five domains: edge-to-edge leaflet repair, tricuspid annuloplasty, caval implants, spacer, and total valve replacement. Each transcatheter intervention needs specific imaging protocols for assessing the anatomical feasibility and consequentially predicting the procedural success. This review summarizes the available multimodality imaging tools for screening patients with TR, and identifies anatomical characteristics to choose the best option for the patient.